FAKTOR–FAKTOR YANG MENDORONG IBU RUMAH TANGGA BERKERJA DI KELURAHAN PULAU BODI KECEMATAN BANGKINANG KABUPATEN KAMPAR - Nurzalina Nurzalina; Wilson Wilson; Jaspar Jas (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2020)
Abstract: This research is motivated by the factors that encourage housewives to work in Pulau Bodi Village, Bangkinang District, Kampar Regency, so that the aim is to determine the most dominant factor in encouraging housewives to work in Pulau Bodi Village, Bangkinang District, Kampar Regency. The population in this study were 67 housewives who worked as farmers. The sample of this study were 40 people and 20 working housewives. The sample used was simple random sampling. The data processing technique in this research is to verify data, group items based on indicators, make a preparation table for raw scores, tabulate by making a list of frequency distribution based on indicators and using percentages. Data analysis through quantitative descriptive analysis. The weight of each answer is Very True (SB) with a score of 5, True (B) with a score of 4, Not True (KB) with a score of 3, Not True (TB) with a score of 2, Very False (STB) with a score of 1 The validity test was carried out on 20 housewives who work in the Bodi Island Village, Bangkinang District, Kampar Regency. With a critical r value of 0.444. Of the 42 statement items tested, 6 statements were invalid. Researchers discard all invalid statements, because 6 invalid statements are discarded and do not result in other items. Based on these results, the factors that encourage housewives to work in the Pulau Bodi Village, Bangkinang District, Kampar Regency are classified as high, with the highest indicator being socio-cultural factors, compared to economic factors.Key Words: Perception, Perception of Citizens Learning